49.8k views
10 votes
What are the solutions to the following system of equations? Select the correct answer below.

y = x2 - 4x + 3
2x + y = 6
A) (-1,8) and (3,0)
B) (-1, 3) and (8,0)
C) (0,8) and (3, -1)
D) (3, 8) and (-1,0)

User Babbitt
by
4.6k points

1 Answer

6 votes

Answer:

A

Explanation:

we can conclude from the second equation that when

2x + y = 6 then y = 6 - 2x. so instead of y in the first equation we use 6 - 2x.

now the equation would look like this : 6 - 2x = x^2 - 4x + 3 .

then we bring everything to one side of the equation : x^2 - 2x - 3 .

now we'll have two results for x ( because x^2 - 2x - 3 = 0 has 2 answers )

one of them is -1 and other one is 3.

if we put them in the first equation we will have 8 and 0 for y.

so A is the answer

User Nicoretti
by
5.2k points